Pemetaan Riset Teknologi 5G - Awangga Febian Surya Admaja (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2018)
This study aims to provide an overview of how the 5G technology study evolved from the range of 2013 to 2017. The publication mapping is expected to illustrate the next step in determining the contribution of 5G technology. The mapping is done by taking online databases from a source, in this study using a Scopus database. The obtained databases are sorted based on predetermined keywords then the results are visualized in accordance with the relationship of each data. The results are elaborated qualitatively by looking at the level of contributions, the number of citation collaborations of authors, and so on. Based on the keywords processing, Massive MIMO is the most widely chosen topic in doing research, although according to the telecommunication industry perspective in Indonesia, it is challenging to adopt due to various limitations. *****Kajian ini bertujuan untuk memberikan gambaran bagaimana kajian teknologi 5G berkembang dari rentang tahun 2013 sampai dengan tahun 2017. Pemetaan tersebut diharapkan dapat memberi gambaran langkah ke depan dalam menentukan kontribusi di teknologi 5G. Pemetaan dilakukan dengan cara mengambil basis data online dari salah satu sumber, dalam kajian ini menggunakan basis data Scopus. Data tersebut di-query berdasarkan kebutuhan antar data dan hubungan dari masing-masing data tersebut divisualisasikan. Hasil tersebut dijabarkan secara kualitatif dengan melihat tingkat kontribusi, jumlah sitasi kolaborasi penulis, dan sebagainya. Berdasarkan pengolahan kata kunci, Massive MIMO merupakan topik yang paling banyak dipilih dalam melakukan riset, meskipun dari sudut pandang industri telekomunikasi di Indonesia hal ini sangat susah diadopsi karena berbagai keterbatasan.